(untitled) (Education in the 21st Century, 2023)
The problem of this study. The article discusses the problem of studying the relationship of aesthetic and social consciousness, the methodology of teaching the subject in pedagogical discourse, modern approaches to studying problems related to issues of aesthetics, aesthetic taste, aesthetic categories, art history and philosophy, the relationship of aesthetic and the formation of public opinion and consciousness. Actual research on this issue. The history of world cultural heritage from ancient centuries to the present, from the scientific works of Plato and Aristotle to this day, reveals a tendency to influence public opinion and consciousness through art, aesthetic sensations and the development of aesthetic taste. Modern society needs to develop new methods of teaching problems in higher education institutions. The purpose of this study is to identify new methods of teaching the subject in pedagogical discourse, modern approaches to studying problems related to issues of aesthetics, aesthetic taste, aesthetic categories, history and philosophy of art, the relationship of aesthetic and the formation of public opinion and consciousness. Novelty. The article offers the latest teaching options for such scientific subjects as <Aesthetic and social consciousness>, which should contribute to the development of worldview, spiritual and aesthetic growth of students and students in general.